Efektivitas Teknik Cognitive Restructuring Untuk Meningkatkan Self Regulation Anak Didik Pemasyarakatan (Andikpas) di LPKA Klas I Palembang - Meity Rahmatiya; Suryati Suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
The thesis entitled "Effectiveness of Cognitive Restructuring Techniques to Improve Student Self Regulation (Andikpas) in Class 1 LPKA Palembang". This thesis aims to determine the level of self-regulation andikpas and the effectiveness of group counseling with the Cognitive Restructuring technique to improve andikpas self-regulation in LPKA Class 1 Palembang. The research approach used is quantitative research with the type of experimental research in which the research design is One Group Pretest-Postest design. The population of 276 people using the purposive sampling technique was 14 people. The instruments used in this research were questionnaires and documentation. The analysis used Wilcoxon test. The results of the first study which show the results of the level of Self Regulation andikpas in LPKA Class 1 Palembang are in the medium category with a percentage of 71%, the second is based on the results of the Wilcoxon Test showing that symp.sig (2-tailed) is worth .001. Value of .001 <0.05, it can be concluded that Ha is accepted and Ho is rejected, which means that there is a difference from the results of the Pretest and Posttest. So it was concluded that group counseling is effective for increasing Andikpas Self Regulation in Class 1 LPKA Palembang.